2017
DOI: 10.1186/s12890-016-0344-8
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices regarding tuberculosis care among health workers in Southern Mozambique

Abstract: BackgroundTuberculosis (TB) control is more likely to be achieved if the level of knowledge regarding TB is increased among health workers managing high-risk groups. No formal assessments regarding knowledge, attitudes and practises of health workers about TB have been published for Mozambique, a country facing challenges in the fight against TB, with a fragile health system and considerable work overload of health personnel. The main objective of the study was to determine the level of knowledge, identify att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
54
5
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 27 publications
18
54
5
8
Order By: Relevance
“…In a previous national interview study in 2001/2002 of 492 health care workers (HCWs) in Iraq, a good level (almost 100%) of knowledge was reported among the majority of both groups, which was considered by the researchers as an indication of the good impact of the national TB program in Iraq 4 . However, these findings are not consistent with finding in most reviewed surveys in other countries [5][6][7][8][9][10][11][12] . A nationwide survey in Iran among 1016 participants working in TB laboratory in 50 universities in Iran indicated lack of optimum practice among HCWs regarding TB in Iran.…”
Section: Introductioncontrasting
confidence: 83%
See 2 more Smart Citations
“…In a previous national interview study in 2001/2002 of 492 health care workers (HCWs) in Iraq, a good level (almost 100%) of knowledge was reported among the majority of both groups, which was considered by the researchers as an indication of the good impact of the national TB program in Iraq 4 . However, these findings are not consistent with finding in most reviewed surveys in other countries [5][6][7][8][9][10][11][12] . A nationwide survey in Iran among 1016 participants working in TB laboratory in 50 universities in Iran indicated lack of optimum practice among HCWs regarding TB in Iran.…”
Section: Introductioncontrasting
confidence: 83%
“…Similarly, a recent study among HCWs in Mozambique reported a low score of 14.89 points out of a total possible 26 points which indicates gaps in HCWs knowledge. 9 The significant association of knowledge with age and duration of work found in the present study was reported in most reviewed studies 4,7 , and this might be related to the small sample size with wide age range (25-59) in the present study.…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…The literature emphasizes that managers need to make efforts to capture more resources for action and to obtain new knowledge (1) , which have been of great importance in the detection and reporting of cases (13) . A study carried out in Mozambique revealed that health professionals still have difficulties in knowing about patient characteristics, diagnosis and treatment of TB (14) , a situation that suggests the need for constant training of professionals in this area.…”
Section: Discussionmentioning
confidence: 99%
“…The words of MS13, MTS15 and MTS8 leave traces that the lack of transport and the long distances associated with the absence of laboratories lead to an increase in the spread of the disease and higher costs for patients undergoing treatment (19)(20) . Likewise, the lack of transportation is pointed out by some authors as an obstacle in adherence to treatment (21) ; and in a context such as Mozambique, where transport is a serious problem and where reported cases annually are less than estimated (14) , the mobilization of various sectors such as education, health and transport to control TB can be important in increasing detection and reporting of cases (21) . A review of the detection and reporting system should be done by focusing on the increase of laboratories and qualified professionals as well as a double registration of cases that guarantees the validity of information beyond the modernization of the means of records.…”
Section: Discussionmentioning
confidence: 99%